Fire Whirl Evolution Observed during a Valley Wind-Sea Breeze Reversal - Daisuke Seto; Craig B. Clements (Journal of Combustion)
This observational study documented the atmospheric environment of a prescribed fire conducted in a narrow valley when a small fire whirl developed during a mesoscale wind reversal. Based on analysis of in situ meteorological measurements, it is hypothesized that the fire whirl formed due to the presence of strong vertical wind shear caused by the interaction of a sea breeze front with a weaker up-valley wind. Vorticity generated by the interaction of the wind shear and the fire front was estimated to be ~0.2 s−1. Peak turbulence kinetic energy was caused by the wind shear rather than the buoyancy generated by the fire front. It was also found that the convective Froude number itself may not be sufficient for fire whirl prediction since it is less relevant to the near-surface boundary-layer turbulence generated by environmental wind shear. Observations from this case study indicate that even low-intensity prescribed fires can result in the formation of fire whirls due to mesoscale changes in the ambient atmospheric environment.